Quantified power Doppler as a predictor of delayed graft function after renal transplantation - Contti, Mariana Moraes [UNESP]; Garcia, Paula Dalsoglio [UNESP]; Kojima, Cristiane Akemi [UNESP]; Nga, Hong Si [UNESP]; Cordeiro de Carvalho, Maria Fernanda [UNESP]; Modelli de Andrade, Luis Gustavo [UNESP] (Springer, 2015)
No safe ultrasound (US) parameters have been established to differentiate the causes of graft dysfunction.To define US parameters and identify the predictors of normal graft evolution, delayed graft function (DGF), and rejection at the early period after kidney transplantation.Between June 2012 and August 2013, 79 renal transplant recipients underwent US examination 1-3 days posttransplantation. Resistive index (RI), power Doppler (PD), and RI + PD (quantified PD) were assessed. Patients were allocated into three groups: normal graft evolution, DGF, and rejection.Resistive index of upper and middle segments and PD were higher in the DGF group than in the normal group. ROC curve analysis revealed that RI + PD was the index that best correlated with DGF (cutoff = 0.84). In the high RI + PD group, time to renal function recovery (6.33 +/- A 6.5 days) and number of dialysis sessions (2.81 +/- A 2.8) were greater than in the low RI + PD group (2.11 +/- A 5.3 days and 0.69 +/- A 1.5 sessions, respectively), p = 0.0001. Multivariate analysis showed that high donor final creatinine with a relative risk (RR) of 19.7 (2.01-184.7, p = 0.009) and older donor age (RR = 1.17 (1.04-1.32), p = 0.007) correlated with risk DGF.Quantified PD (RI + PD) was the best DGF predictor. PD quantification has not been previously reported .
Keywords: Power Doppler; Resistive index; AKI; Delayed graft function; Renal transplantation